GLOBALIZATION, EXCLUSION AND SOCIAL DEVELOPMENT AND ITS BRANDS IN CONTEMPORARY SOCIETY (Revista Paradigma, 2020)
Globally, the phenomenon of globalization and the unfolding of financial capitalism have contributed to the constitution of a huge range of subjects deprived of their socio-economic rights as well as their citizenship. In the meantime, in order to ensure social protection and fulfillment of the basic needs of these individuals, numerous actions and measures have been undertaken on behalf of the Welfare State for this purpose. Notwithstanding this, many of these initiatives are notoriously welfare-oriented and clientelistic, and are therefore unable to lead such individuals to autonomy from the welfare programs offered by the state.